The Impact of Democratic and Autocratic Leadership Styles on Teacher Performance in Basic Education School - Ximenes, Salvador Magno; Silva, Manuel Belo Da (Researchparks Publishing, 2024)
This study examines the impact of democratic and autocratic leadership styles on teacher performance in basic education schools in Baucau town, Timor-Leste. Leadership style plays a pivotal role in educational outcomes, yet limited research has explored its influence in the Timor-Leste context. Employing a quantitative approach, data were collected via teacher questionnaires and analyzed using multiple linear regression in SPSS. Three hypotheses were tested: the individual impact of autocratic (H1) and democratic (H2) leadership styles, and their combined impact (H3) on teacher performance. Results reveal that while democratic leadership significantly enhances teacher performance, autocratic leadership does not have a significant effect. However, both styles together have a combined impact. These findings underscore the importance of fostering democratic leadership to create inclusive and collaborative school environments. The study recommends that national education authorities prioritize leadership training and policy reforms to enhance democratic leadership practices.